The Impact of Eizenkraft model in the Development of Multiple Intelligences among Preparatory School Students and developing creative mind through varied activities - Al – Khafaji , Haifa Amran Mousa; Hussein, Zeina Ghani Abdul; Al-Issawi, Saif Tariq (International Journal of Psychosocial Rehabilitation, 2020)
Creativity requires a certain state of mind. an increase in positive emotions leads to a broader thought-action repertoire. This ultimately leads to more creative, flexible, integrative and open thinking patterns. The aim of the research is to find out the effect of the Eizenkraft model on achievement of Rhetoric material and developing the skills of the creative thinking of fifth grade female students in the rhetoric material. The researcher adopted an experimental design in the field of experimental designs with partial control and a final test for the two research groups, one experimental and one control. In order to achieve the research objective, the researcher presented the null hypothesis (there is no statistically significant difference between (0.05) The researcher chose randomly (Shatt Al-Arab secondary school) rewarded the researcher with some variables that may affect the results of the experiment. The researcher used the following statistical means: (the independent test of two independent samples, the Kay square (Ka 2), the Pearson correlation coefficient, the coefficient of difficulty and discrimination, and the equation of the number of female students in the first semester of the fifth grade. The effectiveness of the incorrect alternatives).